Efeitos dos agrotóxicos Kraft® 36 EC (abamectina) e Score® 250 EC (difenoconazol), isolados e em misturas, sobre organismos zooplanctônicos - Moreira, Raquel Aparecida (2017)
Toxic effects of the pesticides Kraft® 36 EC (i.a. abamectina) and Score® 250 EC (i.a. difenoconazol), isolated and in mixtures were evaluated on zoplanktonic organisms. Daphnia magna was used as test-organism to evaluate pesticide effects using the biochemical biomarkers cholinesterase (ChE), catalase (CAT) and lipid peroxidation (LPO), besides energy-related parameters (total proteins and lipids) together and energy consumption (EC). Possible effects of agrochemicals on tropical aquatic ecosystems were simulated and evaluated by acute and chronic toxicity tests with surface runoff from soil experimentally contaminated with both agrochemicals. The native cladoceran Macrothrix flabelligera was used as test-organism. Potential risks related to exposure to isolated compounds and their combinations were evaluated through microcosm experiments. A review of literature was performed to analyze the use of rotifers species as test-organisms for pesticide toxicity evaluation in aquatic ecosystems with emphasis on tropical configurations. It was found that there is great potential for using rotifers as test-organisms for toxicity evaluations and risk assessment. An evidence of this potential was a higher sensitivity of native species exposed to fungicides if compared to D. magna. The isolated compounds did not have effects on cholinesterase (ChE) and catalase (CAT), but their mixture induced an increase on these biochemical. Lipid peroxidation (LPO) was induced for D. magna was exposed to the fungicide. Reproductive output was small but protein was not quantitatively affected, but the highest combination of both pesticides resulted increased lipid reserves. Consumed energy was highly affected and stimulated in all treatments for both, isolated compounds and mixtures. For M. flabelligera, tests with mixtures revealed a concentration dependent deviation (DL) by IA model, with antagonism in low and synergism in high mixture concentrations. The microcosms receiving runoff from experimental soil contaminated with individual pesticides did not cause toxicity to the test-organism, however their mixture caused immobility. The microcosm treated by spray drift with both pesticides showed the highest toxicity effects. Our results suggest potential risk of the selected pesticides in environmentally relevant concentrations, especially if occurring together.